Political and sociodemographic challenges of child malnutrition in African Sahelian countries and Corn of Africa - (:unkn) unknown (My University, 2017)
Continuous food and nutrition insecurity that affect lives of 155 millions of children in the world including about 59 million in African countries mostly in the Sahel and horn of Africa represent a critical public health and underdevelopment problem which creates a deep worldwide collective moral issue within the new global transformative agenda for the universal prosperity (no one is left behind) and child rights for survival, development and protection.Under five child malnutrition characterized by stunting, underweight or wasting increase the risk of child morbidity and mortality, handicap readiness of learning and professional skills and impact on economic development of the country resulting to a vicious circle of poverty and fragility of the family and causing international migrations.Four countries mostly affected by child malnutrition in the Sahel and horn of Africa that we have selected for this study (Burkina Faso, Niger, Senegal and Ethiopia) in comparison to Ghana are facing the severity of climatic and geo-ecologic environment, political instability, weak economic and social development and the gap of nutritional governance undermined by the lack of political, legal and financial commitments of Government and the limited institutional capacities to combat strongly undernutrition.In addition to food insecurity, malnourished children and their families are confronted to bottlenecks of supply and demand of access and use of community based basic social services, to the household poverty, the poor family social status, to demographic burden, gender based inequality, heavy social norms, traditional cultural and believes and ignorance of malnutrition which cause inadequate behavioral practices of child feeding and nutrition, child health care including unsafety water & sanitation conditions that facilitate diseases & malnutrition.Strengthening effective political engagement, accountable governance and massive financial investmen
Keywords: African Research